Promosi Sentra Tenun Desa Kaliuda Sumba Timur Sebagai Wisata Budaya (Culture Tourism) Bagi Generasi Milenial Di Indonesia - Enos, Yeremia; Magetanapuang, Joachim David (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
East Nusa Tenggara has a lot of potential has three industrial focuses sectorsuch as salt, sugar and traditional weaving cloth. Traditional weaving cloth in EastSumba has a variety difference of motifs because each island in East NusaTenggara has different motif. The weaving center at Kaliuda Village has the highestquality in East Sumba, because it is flexible, does not fade, light and can be usedas normal clothing. 90% of Kaliuda Village people are traditional weavers, sowoven cloth is the main source of income in this village Although woven cloth ofKaliuda has its high quality, and beautiful motifs but unfortunately this weavingcenter of Kaliuda Village, East Sumba, is still not well known to many people, onlywoven fabric lovers and collectors knows about it, The purpose of this research isto make persuasive approach to the millennial generation towards the preservationof the weaving culture as well as provide information also attract public interest toknow more about weaving center in Kaliuda Village, East Sumba which can bevisited as Culture Tourism through promotional media. In designing thispromotional media, the researchers uses theories that are believed to be the basis,such as communication theory, advertising theory, and visual communicationdesign theories.